Islamic Education with an Ecological Perspective: Quranic Foundations, Environmental Ethics, and Pathways toward Sustainable Development - Hamdan, Hamdan (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
The escalating global environmental crisis necessitates the mobilization of moral and spiritual resources beyond scientific and regulatory frameworks. Islam, with approximately 1.8 billion adherents, possesses a comprehensive ecological ethic, yet existing scholarship on its integration into Islamic education remains fragmented across theological, pedagogical, and policy domains. No prior systematic review has synthesized these three interconnected domains into a unified analytical framework. This study addresses this gap by conducting a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines, examining three interrelated pillars: (1) Quranic ecological ethics as theological foundations (2) pedagogical implementation within Islamic educational institutions, and (3) policy and practical pathways to sustainable development. A systematic search of the Scopus database (2009–2026) using targeted keywords yielded 56 records. After screening, eligibility assessment, and quality appraisal using a modified Mixed Methods Appraisal Tool (MMAT), 34 peer-reviewed publications were included in the thematic synthesis. The findings reveal that the Quran articulates a coherent ecological ethic grounded in khilafah (stewardship), tawhid (divine unity), mizan (cosmic balance), and the prohibition of israf (wastefulness). Innovative institutional models—including eco-pesantren, eco-tahfiz, and eco-madrasah in Indonesia and Malaysia—have successfully bridged religious formation and environmental literacy. Furthermore, strong alignment between Quranic environmental values and the United Nations Sustainable Development Goals positions Islamic educational institutions as underutilized platforms for advancing sustainability. Limitations include exclusive reliance on Scopus, language restrictions, and geographical concentration in Southeast Asia. Future research should prioritize longitudinal quantitative studies and comparative analyses across diverse Islamic educational contexts.